Teaching intercultural communication through associative fields of professional vocabulary - Stozhok, Ekaterina Viktorovna; Khalevina, Svetlana Nikolaevna; Kozlovtseva, Nina Aleksandrovna; Glushkova, Nadezhda Mamatkulovna (SHS web of conferences, 2021)
In the era of globalization and social distancing, intercultural dialogue plays a crucial role and requires a thorough reinterpretation. It is impossible without foreign language proficiency. Therefore, teaching foreign languages is a key to professional competency and personal growth. Language reflects the culture and functions as a universal tool of mutual understanding. It makes it possible to embrace the interlocutor’s mentality through grasping the peculiarities of the language. The proposed article is devoted to the validity study of the associative field technique. Its application contributes to the successful memorizing of terms and terminological expressions in a foreign language. The research considers the corresponding theoretical background devoted to the issues of intercultural communication, associative fields, and metaphorization of terms and terminological expressions in English. The methods applied in the study include comparative analysis, the method of continuous sampling, and a questionnaire survey. After the survey, the authors identified the terms that evoke associations with the notions “death” and “dead”. The article contains a number of interim conclusions with a further perspective on this issue. It is determined that the notion of “death” stands out as a representative of the “naïve” picture of the world and an initially expressive concept. In the case of a formal concept, the notion functions as a successful component of terms, especially metaphorical ones. The results of the study may be implemented in teaching a foreign language and intercultural communication, as well as in comparative linguistics and cultural studies.